Integral Assessment of Ethnic Tourism in Ukraine: Resource Provision and Regional Features - Liudmyla NIEMETS; Yurii KANDYBA; Pavlo KOBYLIN; Sergiy KOSTRIKOV; Nataliya DOBROVOLSKAYA; Ievgeniia TELEBIENIEVA (Communications of International Proceedings, 2021)
The paper identifies the factors of ethnic tourism development in Ukraine, particularly the complicated historical past, rich cultural heritage, presence of a diaspora of different ethnic groups in Ukraine, etc. The characteristic features of ethno-tourist regions of Ukraine have been found in the context of its historical-geographical and ethnographic zoning – Western, Bukovynian, Transcarpathian, Slobidsko-Naddnipryansky, Southern, Crimean ones. The ethno-tourist resources of Ukraine's regions – monuments of folklore, historical and ethnographic festivals, monuments of material culture, folk arts and crafts, monuments of folk architecture, archeological objects are characterized. A point assessment of ethno-tourist resources of Ukraine's regions has been made.
Keywords: ethnic tourism; ethnographic tourism; nostalgic tourism; cultural tourism; ethno-touristic resources of Ukraine.